Ein regulatives Vertragsrecht für die Datenwirtschaft Vertragsrechtliche Optionen zur Vermeidung von Effizienzverlusten bei der (Weiter-)Verwertung maschinengenerierter Daten in der Industrie 4.0 - Wunner, Katharina (Recht und Digitalisierung | Digitization and the Law, 2022)
How can access to machine-generated, non-personal industry data be improved? The author addresses this question on the basis of an economically justified need for regulation in the digital economy. With a view to the deficits of previous approaches under intellectual property and competition law, she presents a data access regime under contract law. This operates on the basis of an alternative understanding of contract theory and the idea of a modern private law that is not only dedicated to the freedom of the individual, but is also a means of controlling behaviour. Contractual data access rights are therefore based on a "regulative contract law for the data economy".